Carotenoid composition of hydroponic leafy vegetables - Kimura, Mieko [UNESP]; Rodriguez-Amaya, Delia B. (American Chemical Society (ACS), 2003)
Because hydroponic production of vegetables is becoming more common, the carotenoid composition of hydroponic leafy vegetables commercialized in Campinas, Brazil, was determined. All samples were collected and analyzed in winter. Lactucaxanthin was quantified for the first time and was found to have concentrations similar to that of neoxanthin in the four types of lettuce analyzed. Lutein predominated in cress, chicory, and roquette (75.4 ± 10.2, 57.0 ± 10.3, and 52.2 ± 12.6 μg/g, respectively). In the lactucaxanthin-containing lettuces, β-carotene and lutein were the principal carotenoids (ranging from 9.9 ± 1.5 to 24.6 ± 3.1 μg/g and from 10.2 ± 1.0 to 22.9 ± 2.6 μg/g, respectively). Comparison of hydroponic and field-produced curly lettuce, taken from neighboring farms, showed that the hydroponic lettuce had significantly lower lutein, β-carotene, violaxanthin, and neoxanthin contents than the conventionally produced lettuce. Because the hydroponic farm had a polyethylene covering, less exposure to sunlight and lower temperatures may have decreased carotenogenesis.
Keywords: Carotenoids; Hydroponic; Leafy vegetables; beta carotene; carotenoid; neoxanthin; plant extract; tunaxanthin f; unclassified drug; violaxanthin; xanthophyll; Brazil; chemical composition; chemical structure; chicory; concentration (parameters); cress; hydroponics; leafy vegetable; lettuce; nonhuman; quantitative analysis; structure analysis; sunlight; temperature dependence; winter; Antioxidants; Food Analysis; Hydroponics; Lettuce; Vegetables; Cichorium intybus; Lactuca